2014
DOI: 10.1007/s10452-014-9492-1
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of zebra mussels to act as shelters from fish predators differs between native and invasive amphipod prey

Abstract: Biological invasions cause organisms to face new predators, but also supply new anti-predator shelters provided by alien ecosystem engineers. We checked the level of anti-predator protection provided to three gammarid species by an invasive PontoCaspian zebra mussel Dreissena polymorpha, known for its habitat modification abilities. We used gammarids differing in their origin and level of association with mussels: Ponto-Caspian aliens Dikerogammarus villosus (commonly occurring in mussel beds) and Pontogammaru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 58 publications
3
53
0
Order By: Relevance
“…Kobak et al (2014) showed that sand does not provide gammarids with effective protection against goby. Thus, the negative effect of the stronger competitor upon P. robustoides, though reduced in the presence of a higher predator, still resulted in the increased mortality of the weaker species in the unfavorable substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Kobak et al (2014) showed that sand does not provide gammarids with effective protection against goby. Thus, the negative effect of the stronger competitor upon P. robustoides, though reduced in the presence of a higher predator, still resulted in the increased mortality of the weaker species in the unfavorable substrate.…”
Section: Discussionmentioning
confidence: 99%
“…In an area rich in alternative food resources, the predation pressure on amphipods can be rather low. Furthermore, D. villosus is able to utilize available anti-predator shelters, such as stones and zebra mussel beds, more efficiently than other amphipods (Kinzler & Maier, 2006;Kobak et al, 2014). The presence of food was also found to inhibit avoidance reactions of Gammarus pulex to fish predators (Szokoli et al, 2015), confirming that food cues can constitute a stronger stimulus than predator kairomones.…”
Section: Discussionmentioning
confidence: 82%
“…In such a situation, amphipods attracted to fish may benefit from feeding directly on fish faeces or from finding an area rich in their prey. Apparently, such behaviour seems to be associated with an increased risk, however, experimental data (Błońska et al, 2015) indicate that D. villosus is not an optimal prey item for fish, having harder exoskeleton than other freshwater amphipods, which may result in the lower predation pressure on this species (Kobak et al, 2014). In an area rich in alternative food resources, the predation pressure on amphipods can be rather low.…”
Section: Discussionmentioning
confidence: 99%
“…This bivalve can be beneficial for many invasive (Ricciardi & MacIsaac, 2000) and native (Karatayev, Burlakova & Padilla, 2002; Gergs & Rothhaupt, 2008) macroinvertebrates (Table 1) by providing them with suitable food (e.g. mussel pseudofaeces) and efficient antipredator shelters in a 3D structure of shells and byssally attached mussels (González & Burkart, 2004; Kobak, Jermacz & Płąchocki, 2014). Therefore, the abundance, biomass and richness of the bottom fauna associated with mussel colonies, including chironomids, oligochaetes, gastropods, amphipods and mayflies, is usually greater than in areas adjacent to mussel beds (Wolnomiejski, 1970; Karatayev, Burlakova & Padilla, 2002; González & Burkart, 2004; Kestrup & Ricciardi, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Zebra mussel colonies often occur on sandy substratum, with bivalves attached to one another (Garton, McMahon & Stoeckmann, 2013). Sand provides invertebrates with minimum antipredation protection (Kinzler & Maier, 2006; Kobak, Jermacz & Płąchocki, 2014), constituting potentially the easiest feeding area for fish. Thus, we compared goby feeding in a mussel bed with their performance on the sandy substratum that often occurs in the vicinity of mussel colonies and constitutes the closest alternative and the easiest feeding ground for the fish.…”
Section: Introductionmentioning
confidence: 99%